Leukocyte Profile of Mice Infected with Plasmodium berghei and Treated with Aqueous Extract of Strychnos Ligustrina and Its Combination with Dihydroartemisinin Piperaquine Phosphate (DHP) - Umi Cahyaningsih; Siti Sa'diah; Wasrin Syafii; Rita Kartika Sari; Arifin Budiman Nugraha (Jurnal Sain Veteriner, 2023)
Malaria is still one of the most highly pathogenic diseases, which remains a significant problem for public health. Natural compounds are alternative ways as an antimalarial compound that are applied for the artemisinin combination. The aim of this study was to determine the effect of a combination of S. ligustrina extract and DHP on the differential leukocytes percentages. This study used 100 mice which were divided into five groups. Group A and B were used for the healthy mice and infected-untreated groups, respectively. Group C used as a controlled drug, received 222 mg/kg BW of DHP. Group D received 300 mg/kg BW of aqueous extract of S. ligustrina. Group E received a combination between 111 mg/kg BW of DHP and 200 mg/kg BW of aqueous extract S. ligustrina. The findings demonstrated that DHP and S. ligustrina extract had an impact on neutrophils, lymphocytes, inhibition, and percentages of parasitemia. The findings revealed that treatment groups C, D, and E reduced the percentage of parasitemia. The percentage of neutrophils in treated groups was significantly higher than in group A (P<0.05). The percentage of lymphocytes was lower in the treated groups, while the percentages of eosinophils, monocytes, and basophils did not significantly different (P<0.05). This study found that group D and E had the same effect on the leucocyte profile as group C. Our findings suggest that the aqueous extract of S. ligustrina, as well as the combination treatment with DHP, have the potential to lead to the discovery of new antimalarial medicines.